Inovação tecnológica e as questões reflexivas do campo da biossegurança - Navarro, Marli B. M. de Albuquerque; Cardoso, Telma Abdalla de Oliveira; Vital, Nery Cunha; Soares, Bernardo Elias Correa (Estudos Avançados, 2014)
The present paper places new thoughts on technology building processes originated from the dynamics of scientific knowledge production, involving market demands related to industrial interests, to the consumer and to social expectations face to technological innovation, which implies in new challenges to the scientific and academic community as well as new challenges to the production of thought, leading mainly to a perspective of complexity regarding multiple areas and fields of knowledge, particularly the discipline of Biosafety. Through this analytical dynamics, the essential concepts of Biosafety are discussed with regard to its relationship to Bioethics and technological innovation, while being set up by preventive actions and public health policies aimed at the quality of innovative technologic products .